Guided Inquiry with socio-scientific issues approach in Improving Student Chemical Literacy Skills - Mukti, Tania Damayanti; L.F.X, Endang Widjajanti (Jurnal Pendidikan Indonesia, 2025)
The low chemical literacy ability of students is the main problem in chemistry learning today. This study aims to analyze the effectiveness of the guided inquiry learning model with the socio-scientific issues (SSI) approach in improving students' chemical literacy skills. This study uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design to measure the effectiveness of the learning model on salt hydrolysis materials. The research sample was selected using random sampling, with a total of 70 students in grade XI MIPA in one of the high schools. Data collection techniques are carried out through pretest and posttest tests to measure students' chemical literacy skills. Data analysis includes normality tests, homogeneity, and hypothesis tests using parametric statistics. The results of the study show that context-based learning with a guided inquiry model and the SSI approach is effective in improving students' chemical literacy skills. This was shown by a significant improvement in the chemical literacy ability profile in the experimental class compared to the control class, which used a scientific approach. Overall, the percentage of students' chemical literacy abilities increased, with most students being in the good and excellent categories in each topic tested. In addition, students who received learning interventions with SSI-based guided inquiry showed improved higher-order thinking skills and greater awareness of environmental issues. This study has implications that the use of the SSI approach in the guided inquiry model can be an effective alternative learning strategy to improve students' chemical literacy and build their concern for the environment.